Monitoring of labor with WHO modified partogram – A study report - Alauddin, Md; Bal, Runa; De, Arunangsu; Mondal, Parthajit; Chakraborty, Mayoukh (Nepal Journal of Obstetrics and Gynaecology, 2014)
Introduction: Partogram represents labor events. World Health Organisation (WHO) had produced a partogram in the last decade and subsequently modified it to make it easier to use. The present study was conducted to note the effectiveness of the WHO modified partogram. Methods: Altogether 430 primigravida women, at term, having single live fetus in vertex presentation, were included for the study. The women were randomly subdivided into three groups: Group A (180 women) - monitoring of labor done by WHO modified partogram; Group B (150 women)- monitoring of labor done by WHO original partogram and 100 women in Group C (control), the labor would be monitored clinically. The results were noted in each group regarding the length of labor, vaginal delivery, cesarean sections, augmentation of labor etc. The results of Group A were compared with Group B and Group C. Result: The comparison of the results of the Group A and Group B did not reveal any statistically significant difference. The comparison of the results of the Group A and Group C observed that significantly less number of women in Group A (4.44%) was in labor for more than 12 hours than in Group C (18%). The number of vaginal delivery was more and cesarean section was less in Group A than Group C (p < 0.05). More number of women required augmentation of labor in Group C (p